2020
DOI: 10.3390/ijms21124256
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Balm Extract ALS-L1023 Regulates Obesity and Improves Insulin Sensitivity via Activation of Hepatic PPARα in High-Fat Diet-Fed Obese C57BL/6J Mice

Abstract: Our previous studies demonstrated that peroxisome proliferator-activated receptor α (PPARα) activation reduces weight gain and improves insulin sensitivity in obese mice. Since excess lipid accumulation in non-adipose tissues is suggested to be responsible for the development of insulin resistance, this study was undertaken to examine whether the lemon balm extract ALS-L1023 regulates hepatic lipid accumulation, obesity, and insulin resistance and to determine whether its mechanism of action involves PPARα. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…On the contrary, PPARγ facilitates preadipocytes maturation (e.g., C/EBPs) and lipogenesis (e.g., SREBP-1) in the adipose tissue [ 23 , 24 ]. Interestingly, studies from in vitro ligand binding assay and reporter gene assay, harboring PPAR response element, indicated that LBE is capable of binding and transactivating three canonical PPARs [ 12 , 60 ]. In addition, it has been reported that the inhibition of triglyceride accumulation by treatment of lemon balm extract was blocked by pretreatment with GW6471 (a PPARα antagonist) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, PPARγ facilitates preadipocytes maturation (e.g., C/EBPs) and lipogenesis (e.g., SREBP-1) in the adipose tissue [ 23 , 24 ]. Interestingly, studies from in vitro ligand binding assay and reporter gene assay, harboring PPAR response element, indicated that LBE is capable of binding and transactivating three canonical PPARs [ 12 , 60 ]. In addition, it has been reported that the inhibition of triglyceride accumulation by treatment of lemon balm extract was blocked by pretreatment with GW6471 (a PPARα antagonist) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies from in vitro ligand binding assay and reporter gene assay, harboring PPAR response element, indicated that LBE is capable of binding and transactivating three canonical PPARs [ 12 , 60 ]. In addition, it has been reported that the inhibition of triglyceride accumulation by treatment of lemon balm extract was blocked by pretreatment with GW6471 (a PPARα antagonist) [ 12 ]. Therefore, present results showing 1:1, 1:2, 2:1, and 4:1 ratios of M-LB/CS prevented the altered expression of PPARs mRNA in response to HFD imply that M-LB/CS may regulate adipocyte hypertrophy and obesity primarily through modulating PPARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is associated with greater risk of developing blood vessel diseases, such as coronary heart disease and stroke. The activation of hepatic PPARα could ameliorate body weight gain and improve insulin sensitivity in HFD-fed obese mice [33]. Moreover, adipocyte hypertrophy and the functional disorder of adipose tissue, such as reduced adiponectin secretion, have been reported to be associated with obesity [34].…”
Section: Effects Of 8-hepe Extracted From E Pacifica On Metabolic Syndromementioning
confidence: 99%
“…The authors also described that gomisin N inhibits adipogenesis and lipogenesis by enhancing fatty acid oxidation and thermogenesis and may have a potential preventive and therapeutic agent to combat obesity. Lee et al [ 11 ] demonstrated that lemon balm extract regulates obesity and improve insulin sensitivity via activation of hepatic peroxisome proliferator-activated receptor α (PPARα) in high-fat diet-fed obese C57BL/6J mice. The authors described that lemon balm extract reduces lipid accumulation and stimulates PPARα reporter gene expression in HepG2 cells.…”
mentioning
confidence: 99%